Dysfunction of Collaborative Governance in the Handling Policy of Covid-19 at Jambi Province - Kabullah, Muhammad Ichsan; Sudarmoko; Koeswara, Hendri; Rahman, Fajri; Azwar (Jurnal Sosial Humaniora, 2025)
Current research on public administration has generally concluded that collaborative governance is a critical factor in solving the contemporary crisis. Collaborative governance has been suggested as a mechanism that brings state and private stakeholders together in policymaking. Through a case study in the Jambi Province, we find that the collaboration between local governments and society has been effective to solve the crisis because they may share understanding to prioritise the Covid-19 pandemic as a common problem. At the same time, the religious tension also had a positive impact on the collaboration. However, the collaboration performance has followed several challenges such as incompatible procedures, inequality for the same access between individuals, and intervention by local elites.